Creation of Real Servitudes through Contractual Agreement under Kosovo Law and Beyond - Haxhi Gashi; Kastriote Vlahna (Sriwijaya Law Review, 2024)
Real servitudes are property rights in foreigners' things (iura in re aliena), in which the titleholder uses others' property to benefit his property. This research aims to analyse the creation of the right of real servitude based on contract as legal title. The analysis specifically examines the provisions of the law of property and other real rights of Kosovo no. 57/2009 and the law on obligation relations of Kosovo no. 16/2012 that do not provide enough specification and clarifications for the content and this type of contract. The isolated analysis only in the provisions of Kosovo law is insufficient for clarification without comparison with the legislation of other countries. Therefore, the Kosovo law is compared with the civil codes of France, Austria, and Germany, aiming to identify similarities, differences, and legal concepts. The work is based on a literature review and normative, comparative, and empirical methods. The research results answer the questions related to the content, form, and type of the contract as a legal title. It shows that  Kosovo law, even though it has some similarities with the French civil code when it comes to the conditions of the valid contract, however Kosovo law differs as follows: a) the contract is not the only condition for acquiring the right of real servitude, but the registration is also needed, b) the content of contract must be based on the interaction of provisions of the law on property and the law on obligation relations, c) the same contract is obligation relationship in nature, but it also serves for the transfer of right and registration of the real servitudes. In this sense, it is concluded that Kosovo law is closer to the Austrian Civil Code and German Civil Code. However, it is not a pure German legal concept since it requires two contracts: a contract of obligation and a contract of transfer of real rights.